A Look Into the Evolution of Epstein-Barr Virus–Induced Lymphoproliferative Disorders: A Case Study. Issue 5 (1st November 2015) - Ambrosio, Maria Raffaella; Rocca, Bruno Jim; Ginori, Alessandro; Mourmouras, Vasileios; Amato, Teresa; Vindigni, Carla; Lazzi, Stefano; Leoncini, Lorenzo
Abstract: Objectives: Epstein-Barr virus (EBV)–induced lymphoproliferative disorders (LPDs) are lymphoid proliferations arising as a result of the loss of an effective EBV-specific cytotoxic T-cell response. LPDs may occur for primary or acquired impairment of the immune system, as well as in some persons without documented immunodeficiency. Methods: In this article, we describe the case of a human immunodeficiency virus–positive patient affected by an EBV-LPD of the stomach who developed a nodal diffuse large B-cell lymphoma with complex morphologic and molecular features. Results: GeneScan analysis of the gastric specimen identified two different heavy-chain immunoglobulin gene ( IGH ) rearrangements characterized by a dominant peak of 285 base pairs (bp) in length and a smaller peak of 266 bp in length. In the lymph node sample, IGH evaluation also demonstrated two different peaks; however, the main peak corresponded to the minor peak detected in the EBV-LPD specimen at the diagnosis. In addition, a monoclonal immunoglobulin light chain gene ( IGL ) rearrangement was also found. We also demonstrated that the major peak in the stomach corresponded to the EBV-positive population observed in the histologic sections. Conclusions: This case may provide additional insights to better understanding the "hit-and-run" role for EBV in lymphomagenesis. However, we could not exclude that our findings represent the co-occurrence of two unrelated B-cell neoplasms rather than a progression from an EBV-positive neoplasm to an EBV-negative one.